2010
DOI: 10.1074/jbc.m110.127936
|View full text |Cite
|
Sign up to set email alerts
|

Serine Residues in the Cytosolic Tail of the T-cell Antigen Receptor α-Chain Mediate Ubiquitination and Endoplasmic Reticulum-associated Degradation of the Unassembled Protein

Abstract: The T-cell antigen receptor (TCR) ␣-chain (TCR␣) is a type I integral membrane protein that becomes ubiquitinated and targeted to the endoplasmic reticulum (ER)-associated degradation (ERAD) pathway when it fails to assemble into the heteromeric TCR complex. Remarkably, TCR␣ has a cytosolic tail of only five amino acid residues (i.e. RLWSS), none of which is the conventional ubiquitin acceptor, lysine. Herein we report that substitution of two conserved serine residues in the cytosolic tail of TCR␣ to alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 52 publications
(78 reference statements)
2
86
0
4
Order By: Relevance
“…ERAD substrates are ubiquitinated at serine/threonine residues and less frequently at lysine residues (Shimizu et al 2010). This process is apparently different from that of other cytosolic ubiquitination mechanisms Ishikura et al 2010). At the cytosolic face of the ERAD complex, the AAAþ ATPase p97/VCP (Cdc48 in yeast) hexamer directs substrate to be drawn into the cytosol .…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…ERAD substrates are ubiquitinated at serine/threonine residues and less frequently at lysine residues (Shimizu et al 2010). This process is apparently different from that of other cytosolic ubiquitination mechanisms Ishikura et al 2010). At the cytosolic face of the ERAD complex, the AAAþ ATPase p97/VCP (Cdc48 in yeast) hexamer directs substrate to be drawn into the cytosol .…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…Although the ubiquitination and HRD1/UBE2J1-mediated dislocation of a lysineless MHC I HC was unexpected, it was not without precedent. Other HRD1 substrates, TCRα (18) and NS-1 Ig light chain (19), can be ubiquitinated on serine/threonine residues, although the requisite E2 enzymes were not identified. Intriguingly, murine UBE2J2, the closest homolog of UBE2J1, cooperates with murine γ-herpesvirus K3 ligase to ubiquitinate serine and lysine residues on murine MHC I HCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…The only integral membrane protein targeted by the cellular ERAD machinery for which sites of ubiquitination are defined is TCRα, a type I transmembrane glycoprotein targeted by both HRD1 and gp78, and ubiquitinated on its cytosolic tail (18,27). In contrast to MHC I HC, in which the folding defect (degron) appears to be located within the luminal domain, unpaired charged residues in the transmembrane domain of TCRα are essential for ERAD (28), suggesting that location of the degron may be important for determining the site of ubiquitination and ligase involved.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination of the N-terminal amino group was first observed on metazoan myogenic differentiation1 (MyoD; Breitschopf et al, 1998) and subsequently observed on other proteins (for review, see Ciechanover and Ben-Saadon, 2004). Non-Lys ubiquitination was first described on mammalian major histocompatibility complex class I a-chain (Cadwell and Coscoy, 2005) and has been subsequently found on other proteins from metazoans and yeast (Wang et al, 2007(Wang et al, , 2012Ishikura et al, 2010;Shimizu et al, 2010;Domingues and Ryoo, 2012;Kravtsova-Ivantsiv and Ciechanover, 2012;Boban et al, 2015). Such alternativesite ubiquitination involves Ser and/or Thr hydroxyl groups as oxyesters and Cys sulfhydryl groups as thioesters (for review, see Kravtsova-Ivantsiv and Ciechanover, 2012).…”
mentioning
confidence: 99%